Management of fall armyworm, Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) in maize (Zea mays L.) in Indonesia and Thailand via mating disruption: Pengendalian ulat grayak, Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) pada jagung (Zea mays L.) di Indonesia dan Thailand dengan gangguan kawin - Srigiriraju, Lakshmipathi; Broms, Kristin; Sripeangchan, Mongkol; Khampuang, Kankunlanach; Ekalianna, Riedha; Ciptadi, Yulius Dika; Iqbal, Muhamad; Tran, Khai; Clark, Thomas; Sudarsono, Hamim; Meinhold, Peter (Jurnal Entomologi Indonesia, 2024)
The fall armyworm, Spodoptera frugiperda (Smith), has been problematic in Southeast Asia since its invasion in 2019. Fall armyworm management in these areas largely depends on synthetic insecticide application, and alternative management practices are very few and impractical. The demand for new and more sustainable tools for managing this pest has increased. In this study, we tested the mating disruption (MD) efficacy of fall armyworm sex pheromone in low-density polyethylene dispensers containing 2.5 g of blended active ingredients, (Z)-9-tetradecen-1-yl acetate (Z9-14Ac) and (Z)-11-hexadecen-1-yl acetate (Z11-16Ac) in a ratio of 87:13. The primary objective was to evaluate the optimal density of the dispensers/ha and understand the benefits of MD in reducing the damage caused by fall armyworm and associated insecticide applications as compared to conventional growers’ practices in Indonesia and Thailand. Research was conducted at 16 locations across Indonesia and Thailand in 2020 and 2021 in 9-ha treatment plots and compared to conventional growers practice. Trap reduction, a measure of MD, was significantly higher (74–90%) with 30 dispensers/ha than with non-dispenser areas, suggesting high levels of mating suppression. MD’s primary benefit is damage reduction, where 30 dispensers/ha reduced damage caused by fall armyworm larvae by 34–35% while simultaneously enabling a greater than 50% reduction in insecticide usage compared to the conventional growers’ practice. Our results show the effectiveness and feasibility of MD using pheromones as an essential management tactic for fall armyworm. These results represent a potential step towards more efficacious and sustainable pest management in Southeast Asia.